2022
DOI: 10.1101/2022.12.22.22283791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A machine learning-based phenotype for long COVID in children: an EHR-based study from the RECOVER program

Abstract: Background As clinical understanding of pediatric Post-Acute Sequelae of SARS CoV-2 (PASC) develops, and hence the clinical definition evolves, it is desirable to have a method to reliably identify patients who are likely to have post-acute sequelae of SARS CoV-2 (PASC) in health systems data. Methods and Findings In this study, we developed and validated a machine learning algorithm to classify which patients have PASC (distinguishing between Multisystem Inflammatory Syndrome in Children (MIS-C) and non-MIS-C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…We fully recognize the burden of Long COVID on the pediatric population-however, Long COVID appears to present differently in children, and these distinctions likely necessitate one or more separate models. 16 We should note that this exercise in ML-based phenotype reuse is not, and was not intended to be a validation of the accuracy of the phenotype. ML-based computable phenotypes present challenges with performance assessment, 17 and the challenge is even greater in the case of a new disease like Long COVID, where few concrete diagnostic guidelines or gold standards exist.…”
Section: Comparing Model Results In Aou Versus N3cmentioning
confidence: 99%
“…We fully recognize the burden of Long COVID on the pediatric population-however, Long COVID appears to present differently in children, and these distinctions likely necessitate one or more separate models. 16 We should note that this exercise in ML-based phenotype reuse is not, and was not intended to be a validation of the accuracy of the phenotype. ML-based computable phenotypes present challenges with performance assessment, 17 and the challenge is even greater in the case of a new disease like Long COVID, where few concrete diagnostic guidelines or gold standards exist.…”
Section: Comparing Model Results In Aou Versus N3cmentioning
confidence: 99%
“…Validation of these cluster analyses in a larger population is recommended to increase generalizability. Machine learning-based clustering has previously been applied to identify potential PPCC patients based on their clinical records [40], and has also been employed in the identification of PCC phenotypes in adults [30]. However, this method has not yet been performed for PPCC cluster analyses, making it a potentially promising tool.…”
Section: Discussionmentioning
confidence: 99%
“…Our two-pronged approach to identifying Long COVID using clinician chart review and a computable phenotype is a strength of the study as previous research that used diagnosis codes or machine learning algorithms did not incorporate a review of patient charts [19][20] . By incorporating both methods, we were able to qualitatively review cases of discordance.…”
Section: Discussionmentioning
confidence: 99%
“…To improve identification of patients with Long COVID, computable phenotyping techniques, which involve developing a set of rules to identify patients with a disorder, have been used in Long COVID studies. Long COVID phenotypes for adult 19 and pediatric 20 patients have been developed using machine-learning approaches that leverage large numbers of clinical features. For example, in a recent pediatric study, a machine learning algorithm demonstrated high precision in classifying both general and MIS-C-specific forms of PASC, with recall rates of up to 70% 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation